Methodology for Developing Individual Physical Therapy Trajectories Based on the Analysis of Sport-Specific Activity - Vlasov, Maksym (Педагогічна Академія: наукові записки, 2026)
The relevance of this study is determined by the growing intensity and variability of athletic loads, which are accompanied by an increased risk of functional disorders and musculoskeletal injuries, as well as by the limited effectiveness of unified approaches to physical therapy in sports rehabilitation. The absence of systematic consideration of sports activity specifics, biomechanical demands, and individual adaptive responses of athletes reduces the stability of recovery outcomes and increases the probability of injury recurrence. The objective of this article is to provide scientific justification for and develop a methodology for constructing individual physical therapy trajectories for athletes based on analysis of sports activity specifics, taking into account functional, biomechanical, and adaptive characteristics of the organism. Research methods include theoretical analysis and synthesis of scientific approaches to individualization of physical therapy in sports rehabilitation, systematization of sports activity characteristics, logical-structural analysis of principles for utilizing functional and biomechanical assessment results, and the method of theoretical modeling of individual physical therapy trajectories. Research findings demonstrate that individualization of physical therapy is effective when holistically accounting for the type of motor activity, dominant physical qualities, spatial-temporal parameters of movements, load characteristics, and the phase of the training-competition cycle. Utilizing functional and biomechanical analysis results based on the principles of functional relevance, cause-and-effect interpretation, hierarchization of impairments, and dynamic adaptation enables the transition from symptomatic correction to management of athletic motor efficiency. Scientific and practical challenges in implementing individual physical therapy trajectories have been identified, related to coordination of rehabilitation and training loads, limited objectification of return-to-sport readiness criteria, and fragmentation of interdisciplinary interaction. The conclusions confirm the appropriateness of using the proposed methodology as a scientifically grounded foundation for integrating physical therapy and the training process. This contributes to enhanced recovery effectiveness, reduced risk of recurrent injuries, and ensures correspondence of rehabilitation programs to the actual requirements of different sports. Prospects for further research are associated with empirical validation of the developed methodology in athletes of various qualification levels, refinement of quantitative criteria for assessing readiness for athletic loads, and development of interdisciplinary support models in sports rehabilitation.